Comparison of retroperitoneal laparoscopic versus open adrenalectomy for large pheochromocytoma: a single-center retrospective study - Wei Zhu; Shaogang Wang; Guanghui Du; Hailang Liu; Jinjin Lu; Weimin Yang (World Journal of Surgical Oncology, 2019)
Abstract Background It remains unclear whether retroperitoneal laparoscopic adrenalectomy (RLA) is safe and effective for the treatment of large pheochromocytoma (PHEO). This retrospective study aimed to identify the advantages and disadvantages of RLA compared to open adrenalectomy (OA). Methods This study included 147 patients who underwent RLA (n = 101) or OA (n = 46) for PHEO larger than 5 cm. Groups were balanced by propensity score matching (PSM) into 46 pairs. Perioperative variables and long-term follow-up results were compared between the two groups. Results After PSM, patients in the RLA group had a shorter operative time (218 vs. 245 min, P = 0.040), quicker bowel recovery (2 vs. 3 days, P = 0.046), and a shorter hospital stay (8 vs. 9 days, P = 0.010) compared to the OA group. The results of multiple linear regression analyses showed that the operative method (OA vs. RLA) had an influence on the above three postoperative variables (β = 31.84, P = 0.046; β = 0.76, P = 0.044; and β = 1.25, P = 0.025, respectively). There was no significant difference in the proportion of patients with improved blood pressure (82.61% vs. 69.57%, P = 0.143) between the two groups. Conclusions Both RLA and OA provide similar perioperative and long-term outcomes for the surgical management of large PHEO. RLA is an efficacious and safe surgical method for patients with PHEO larger than 5 cm in diameter.